Overtake, resilience and escape: three ecological strategies that define the Pseudomonas-Bacillus interactions - Molina-Santiago, Carlos; Pearson, John R.; De-Vicente-Moreno, Antonio; Romero, Diego (My University, 2018)
Plants are colonized by a vast variety of microbes, some of which promote plant growth and protection against pathogens. One way bacteria have evolved to succeed in this competitive scenario is the formation of biofilms which are communities of cells embedded in an extracellular matrix that protects the cells, modulates the flux of signals and controls cellular differentiation. Pseudomonas and Bacillus are among the most predominant bacterial genera within the group of plant-beneficial bacteria. The study of this interaction highlighted different aspects of how these two microbes manage to live together. Firstly, the absence of extracellular matrix in a B. subtilis (Δmatrix) led P. chlororaphis to penetrate in the Bacillus colony, a protection role mainly associated to the EPS. Time course experiments in confocal laser scanning microscopy using fluorescent-labeled strains defined different stages during the interaction: from the initial growth to the first contact where B. subtilis (Δmatrix) partially penetrated in the P. chlororaphis colony to the final overtaken of the entire B. subtilis (Δmatrix) colony by P. chlororaphis. Second, during the interaction, the 95% of the B. subtilis (Δmatrix) population entered in sporulation. Dual RNA-seq transcriptomic analyses highlighted the induction of the type VI secretion system and general metabolic changes in P. chlororaphis, and a strong repression of the sporulation, the carbon metabolism, oxidative phosphorylation, or the induction of chemotaxis and motility mechanisms, phages and DNA repair machinery in the remaining non-sporulated population of Bacillus cells (5%). Our findings argue in favor of the positive coexistence of these species on plant surfaces by using different strategies: Bacillus enters in two different cellular stages, resilience and escaping, while Pseudomonas deploy the metabolic versatility and the close contact defense mechanisms.
Keywords: Microbiología